Secrets of divine love : a spiritual journey into the heart of Islam - Helwa, A. (Beach: Naulit publishing, 2020)
"This book discusses the deeper dimensions of classical Islamic theology through the lens of spirituality, poetry, and teaching stories from dozens of mystical masters from various world traditions"--
Includes bibliographical references (pages 311-346).
Keywords: Islam -- Doctrines; Mysticism -- Islam